1970
DOI: 10.1001/archpedi.1970.02100050397003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Cell Necrosis in the Newborn

Abstract: One hundred and forty-seven infants who died from birth to 7 days of age were studied for the relation of hepatic cell necrosis to other pathological conditions. Disseminated hepatic necrosis was significantly correlated with congenital heart disease, and hypoplastic left heart complex and coarctation of the aorta were more frequently associated with disseminated hepatic necrosis than were other types of congenital heart disease. The microscopic features of the liver in these types of congenital heart disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1972
1972
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Shiraki (1970), in a parallel study of 146 infants dying from birth to 7 days of age, noted hepatic necrosis in 24-5% and fatty changes in a further 14-3% of cases. He concluded that hypoplastic left heart complex and coarctation of the aorta were more frequently associated with hepatic necrosis than with any other type of congenital heart disease.…”
Section: Discussionmentioning
confidence: 93%
“…Shiraki (1970), in a parallel study of 146 infants dying from birth to 7 days of age, noted hepatic necrosis in 24-5% and fatty changes in a further 14-3% of cases. He concluded that hypoplastic left heart complex and coarctation of the aorta were more frequently associated with hepatic necrosis than with any other type of congenital heart disease.…”
Section: Discussionmentioning
confidence: 93%
“…Breast feeding was established, but tachypnoea developed on day 3. Jaundice was noted by the attending midwife on day 4 and was felt to be physiological. It did not improve, however, and serum bilirubin concentration on day 7 was 615 ,umolVl (565 p.molIl unconjugated).…”
mentioning
confidence: 99%
“…Die von der UAB und den mit ihr kombinierten Herzfehlern hervorgerufenen komplexen hämodynamischen Veränderungen führen zu einer Letalität von 80% im ersten Lebensmonat(1, 2). Beim "hypoplastischen linken Herz-Syndrom" wurden zusätzlich zu der myokardialen Ischämie (41) schwere Lebernekrosen mit Hypoglykämie und hämorrhagischer Diathese beschrieben(42,43).Ein großer Ductus arteriosus persistens scheint einen negativen Einfluß auf die Prognose zu haben, weil die Entwicklung der Kollateralarterien dann nicht stimuliert wird(16). Da der rechte Ventrikel über den Ductus arteriosus persistens die Aorta descendens versorgt ("systemic right ventricle"), führt ein plötzlicher Verschluß des Ductus arteriosus zu einer konservativ nicht beeinflußbaren Herzinsuffizienz.…”
unclassified